Pituitary Adenoma Surgery Survey: Neurosurgical Centers and Pituitary Adenomas. (11th April 2022) - Netuka, David; Grotenhuis, Andre; Foroglou, Nicolas; Zenga, Francesco; Froehlich, Sebastien; Ringel, Florian; Sampron, Nicolas; Thomas, Nick; Komarc, Martin; Majovsky, Martin
Abstract : Objective . Pituitary adenoma surgery has evolved rapidly in recent decades. This study aims to determine current practice across a wide range of European neurosurgical centers. Methods . A list of eligible departments performing pituitary adenoma surgery was created. The survey consisted of 58 questions. For analysis, the departments were divided into four subgroups: academic/nonacademic, high-volume/low-volume, "mainly endoscopic/mainly microscopic practice, " and geographical regions. Results . Data from 254 departments from 34 countries were obtained. In 108 centers (42.5%), <30 pituitary adenomas were operated per year. Twenty (7.9%) centers performed >100 adenoma surgeries per year. Number of neurosurgeons performing endonasal surgeries are as follows: 1 in 24.9% of centers and 2 in 49.8% of centers. All residents assisted endonasal surgeries in 126 centers (49.8%). In 28 centers (21.1%), all residents performed endonasal surgery under supervision during residency. In 141 centers (56.8%), the endoscopic approach was used in >90% of the surgeries. Regular pituitary board (either weekly or once a month) meetings were held in 147 centers (56.3%). Nonfunctioning adenomas represent >70% of pituitary caseload in 149 centers (58.7%). Conclusions . In our survey, most centers perform less than 100 surgeries for pituitary adenomas. In most centers, pituitary surgeries are performed by one or two neurosurgeons. Residents have a limited exposure to this type of surgery, and the formal pituitary board is not a standard. Nonfunctioning adenomas make up most of surgically treated adenomas. This study can serve as a benchmark for further analyses of pituitary adenoma centers in Europe.